Analyzing real-world data to understand COVID-19 vaccination effects on hospitalization rates in patients with solid malignancies - George Dimitrov; Radka Argirova; Trifon Valkov (Biotechnology & Biotechnological Equipment)
The impact of COVID-19 vaccination on hospitalizations in individuals with solid malignancies remains uncertain. This nationwide retrospective study aims to clarify this issue. We analyzed data from 1,126,946 confirmed COVID-19 cases between March 2020 and June 2022, obtained from the Ministry of Health’s United Information Portal. Outcomes were compared between fully vaccinated and non-vaccinated cohorts, stratified by sex, age and viral variant. Among the 1,126,946 confirmed COVID-19 cases, 0.53% (n = 6025) had solid malignancies and comorbidities. Of these, 31.3% (n = 1797) had sole solid malignancies. In this subgroup, 40% (n = 764) required hospitalization, with a median age of 63 years. Unadjusted univariate analysis showed a significant reduction in hospitalization rates among COVID-19 vaccinated patients with isolated solid malignancies [OR 0.2776 (95% CI 0.1621 to 0.4753); p < 0.0001], especially in those aged over 63 [OR 0.5981 (95% CI 0.4244 to 0.8429); p = 0.0033]. Lower ICU admission rates favored vaccinated cohorts [OR 0.3418 (95% CI 0.2023 to 0.5777); p = 0.0001]. These reductions were observed exclusively with mRNA-based vaccines [OR 0.5845 (95% CI 0.4333 to 0.7884); p = 0.0004]. Statistically significant vaccination benefits were found only within the omicron cohort [OR 0.2307 (95% CI 0.13687 to 0.3890); p < 0.0001]. The results from the analysis suggest that individuals with sole solid malignancies face an increased risk of hospitalization and ICU admission. However, these risks can be mitigated through vaccination, particularly with an mRNA-based vaccine, especially in those aged 63 years or older.